ÉTUDE ET SUIVI DES PERFORMANCES DES TRAITEMENTS PRIMAIRE ET SECONDAIRE DES EAUX USEES DE LA STATION D’EPURATION DE MARRAKECH - Merieme Tahri; Majdouline Larif; Hajar Quabli; Mohamed Taky; Mahacine Elamrani; Azzedine El Midaoui; Karima Benazouz; M’hamed Khimani (European Scientific Journal, ESJ, 2015)
The activated sludge technology is an innovative intensive method for treating wastewater. It is well suited to discharges from communities large sizes and very effective for the treatment of carbon, nitrogen and phosphorus. The raw effluent of the WWTP of Marrakech and secondly evaluate the performance of primary processing (TP) which eliminates almost 50% of suspended solids and reduced by about 40% BOD and COD. Finally we will evaluate the purifying efficiency of secondary treatment (TS), the monitoring results show that it is 95% for BOD5, 80% for COD, 70% for TSS, 85% NTK and 55 % for Pt. The obtained results show that except the Pt qui exceeds the standard set at 2 mg/L, the concentration of all the performance indicators at the outlet of biological treatment (secondary) complies with Moroccan and European standards for direct discharges.